THE RELATIONSHIP BETWEEN READABILITY LEVEL OF TEXT MATERIALS AND VOCATIONAL HIGH SCHOOL STUDENTS' READING COMPREHENSION ABILITY IN EFL CLASSROOMS - Hariz, Wildan (2015)
This study aims to investigate the relationship between readability level of text materials and vocational high school students' reading comprehension ability in EFL classrooms. It was based on the underlying theories and current condition regarding the need to investigate the relationship between both variables in Indonesia, in which English is a foreign language. Data were gained from a sample of 30 vocational high school students in an EFL classroom by administering a reading comprehension test and measuring the readability levels of texts on the textbook used in that classroom. Pearson Product Moment formula was used to measure the correlation between both of the results. It was revealed on the findings that there was a negative moderate correlation (-0.504) between the readability level and the vocational students' reading comprehension ability. The present study concluded that readability explains 25.40% vocational students' reading comprehension ability in EFL classrooms.